Measures of health-related quality of life in PCOS women: a systematic review - Behboodi Moghadam Z; Fereidooni B; Saffari M; Montazeri A (Dove Medical Press, 2018)
Zahra Behboodi Moghadam,1 Bita Fereidooni,2 Mohsen Saffari,3 Ali Montazeri4 1Department of Reproductive Health, School of Nursing and Midwifery, Tehran University of Medical Sciences, Tehran, Iran; 2Department of Reproductive Health, School of Nursing and Midwifery, Tehran University of Medical Sciences, Tehran, Iran; 3Health Research Center, Life Style Institute, Baqiyatallah University of Medical Sciences, Tehran, Iran; 4Population Health Research Group, Health Metrics Research Center, Iranian Institute for Health Sciences Research, ACECR, Tehran, Iran Introduction: Polycystic ovary syndrome (PCOS) is associated with biochemical and hormonal disturbance and adverse cosmetic, reproductive, metabolic, and psychological consequences, resulting in reduced health-related quality of life (HRQoL). Various generic and specific questionnaires have been used for assessing different dimensions of HRQoL in PCOS women. The purpose of this systematic review was to identify those general and specific instruments and to determine the factors that affect HRQoL in PCOS women. Materials and methods: The research strategy involved general and specific terms in relation to PCOS women and their QoL. A review was performed on studies that were published between 1945 to 2017 and that were indexed in MEDLINE, ISI Web of Science, and Scopus. A narrative synthesis of the data was provided. Results: In total, 52 studies (9 qualitative and 43 quantitative) were included in the review. The analysis indicated that 3 specific and 5 general instruments were used to measure the QoL in PCOS women. Of these, the 36-Item Short Form Health Survey (SF-36) and the Polycystic Ovary Syndrome Health-Related Quality of Life Questionnaire (PCOSQ) were used most frequently. All studies assessed different aspects of QoL in PCOS women and found that PCOS had negative effects on QoL in this population. Conclusion: The PCOSQ and the SF-36 were used most frequently for the assessment of QoL in PCOS women. Perhaps using either a specific questionnaire solely or a specific questionnaire in conjunction with a generic measure would be more appropriate when measuring QoL in PCOS women. However, both questionnaires showed that they are able to capture different aspects of QoL in PCOS women and to identify areas that can help to improve QoL in these women. Keywords: polycystic ovary syndrome, health-related quality of life, questionnaires, systematic review